Development and out-scaling of Sub1-introgressed submergence tolerant rice in Madagascar - CGIAR Research Program on Rice (2019)
In Madagascar, Sub-1-introgressed lines have passed two seasons of testing. In one trial, three lines superior in performance over local checks were identified after screening 48 Sub1-introgressed lines, under combined effects of cold and flooding. National performance trials are to be conducted for submission to the varietal release committee.